Article Processing Charge for Open Access Articles in Iran - Sohani, Fatemeh; Shekofteh, Maryam; Shahbodaghi, Azam; Jambarsang, Sara (DESIDOC Journal of Library & Information Technology, 2024)
The present research aimed to investigate the Open Access (OA) and non-OA publishing models and the Article Processing Charge (APC) in Iranian researchers’ articles. The study population included all researchers’ articles from Shahid Beheshti University of Medical Sciences (SBMU), Tehran, Iran, indexed in the Scopus database from 2017-2019. The publication model of the articles was determined by referring to the original article, the type of journal, and their APC rate through the journal website, and the country of the journals’ publishers using the Scimago database. The data were analysed using descriptive statistics and SPSS software. Five thousand ninety-seven articles (54.5 %) were published as OA and 4255 articles (45.5 %) as a non-OA. 57.1 % of OA articles were published in APC OA journals, 20.3 % in non-APC OA journals, and 11.7 % in hybrid journals. $ 4,899,027.15 was spent on publishing 3,506 OA articles; the average cost per article was $1,397.32. Publication costs for Iranian researchers are obstacles to publishing OA articles in APC journals. It is necessary to provide sufficient support to researchers by universities and the Ministry of Health and Medical Education of Iran. Considering the low economic capacity of Iranian researchers, international journals should also consider discounts for them.